Complete heart block and asystole following blunt cardiac trauma - Mohamed Morsy; Nephertiti Efeovbokhan; Sunil K. Jha (Greater Baltimore Medical Center, 2015)
Cardiac contusion is a well-recognized complication of blunt chest trauma. Various conduction system disorders have been reported in association with this condition, the most common being right bundle branch block. Complete heart block (CHB) is seen rarely. Most cases of CHB are transient. We present the case of an 80-year-old woman who developed CHB and asystole following blunt cardiac trauma. Malignant cardiac arrhythmias such as CHB can be associated with blunt cardiac trauma. In most cases, CHB is transient resolving in days to weeks. In rare cases, however, CHB leads to asystole. Close monitoring and prompt intervention is thus required.